Evaluasi Sifat Ovisidal dan Nimfasidal Insektisida Buprofezin 100 g/l terhadap Telur dan Nimfa Wereng Coklat, Nilaparvata lugens (Stal.) (Hemiptera: Delphacidae) - EFFENDI, BAEHAKI SUHERLAN; ISWANTO, EKO HARI; HAMZAH, AMIR (Agrotrop : Journal on Agriculture Science; Vol 6 No 2 (2016), 2016)
Evaluation of ovicidal and nymphcidal properties of buprofezin 100 g/linsecticide to eggs and nymphs of brown planthopper, Nilaparvata lugens(Stal.) (Hemiptera: Delphacidae). Research was carried out in screen house ofSukamandi, Indonesian Center for Rice Research (ICRR) in the wet season of 2013. Theresearch used randomized block design with 5 doses levels insecticide treatment of buprofezin100 g/l and four replications. The buprofezin treatments were 250, 500, 750, 1000, and 1500ml/ha compared with control without insecticide. The objective of the research to evaluate ofovicidal and nymphcidal of buprofezin to brown planthopper (BPH). The results showed thatthe ovicidal properties of buprofezin 100 g/l with a range doses of treatments to BPH eggsthat application at 5 days after inoculation with eggs remains in the plant tissue were 39,79-94,88%. The raising ovicidal of buprofezin were 74,84-99,5% that applied at 9 days afterinoculation with eggs remains in the plant tissue. In the other hand the ovicidal properties ofbuprofezin decreased dramatically were 20-48% that applied at 5 days after inoculation andthen BPH eggs removed from plant tissue (dissected) at 9 days after inoculation. The higherovicidal properties of buprofezin is better in the plant tissue than in the dissected eggs treated,because buprofezin working on eggs in plant tissue as a systemic insecticide. The dissectedBPH eggs of rice treated to show the normal eggs shape and no eggs contracted. Theunhatched eggs of buprofezin treatments were milk white due to insecticide effect, sometranslucent color with a red dot as a fertile eggs or without a red dot as unfertile eggs.Buprofezin was the excellent nymphcidal insecticide with the value of the efficacy to BPHnymphs were very high about 87,44 -100% for a range doses treatments. Buprofezin did notresurgence effect, moreover this insecticides still have ovicidal and nimphcidal properties as abasic to reduce offspring of brown planthopper.
Keywords: Buprofezin, ovicidal, nymphcidal, brown planthopper